Charles Wesley's Doctrine of the Holy Spirit: A Vital Resource for the Renewal of Methodism Today - Vickers, Jason E. (The Asbury journal, 2006)
This essay is an extended argument in favor of a recovery of a robust doctrine of the Holy Spirit in Wesleyan-Methodist theology today The argument develops in five stages. First, it shows the significance of the person and work of the Holy Spirit in Charles Wesley's understanding of revelation, the atonement, purification, sanctification and the like. Second, it suggests that contemporary Wesleyan theologians have often ceased attributing these things to d1e presence and work of the Holy Spirit, opting to attribute them in a generic way to grace instead. Third, it provides a conceptual analysis of the difference between the Holy Spirit and grace. Fourth, the essay identifies four factors that have contributed to the domestication of the Holy Spirit in contemporary Wesleyan theology Finally, the essay concludes by suggesting that the one key to the renewal of Methodism is a rediscovery of the doctrine of the Holy Spirit in all its fullness.